Opportunities in UK primary and secondary healthcare settings to prevent alcohol misuse - Otete, Harmony Eroboghene (2016)
Background Alcohol-related deaths and hospital admissions have risen steeply in the United Kingdom and little is known about whether there are opportunities for preventive interventions or opportunities for the earlier detection of alcohol misuse.